2019
DOI: 10.2497/jjspm.66.116
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Cr Diffused Sm<sub>2</sub>Fe<sub>17</sub>N<sub><i>x</i></sub> Core-shell Magnetic Powders by Reduction-Diffusion Process

Abstract: In this work, Cr diffused Sm 2 Fe 17 N x core-shell magnetic powders were prepared by reduction-diffusion (RD) process. Sm 2 Fe 17 coarse, Cr 2 O 3 and Sm 2 O 3 fine powders were pulverized and mixed by ball milling, and the mixed powder was heat treated following Ca addition. Cr can diffuse into Sm 2 Fe 17 powder above 875°C in RD process, and the diffusion distance of Cr increased with increase in RD temperature. Cr diffusion distance into Sm 2 Fe 17 powder was about 1.1-1.2 μm under RD temperature at 875°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…After washing with EG in the GB, the Sm 2 Fe 17 N x / Sm 2 (Fe,M) 17 N x coreshell powders showed higher coercivity than commercial SmFeN powder even after heat-resistance tests in which the powders were annealed at 300°C for 1.5 h under Ar atmosphere. 22,23) We also found that pure SmFeN powder without any additive element prepared by the developed RD process exhibited high coercivity after the heat-resistance test. These results indicated that the improved heat resistance of the SmFeN powder was attributable to washing with EG in a GB.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…After washing with EG in the GB, the Sm 2 Fe 17 N x / Sm 2 (Fe,M) 17 N x coreshell powders showed higher coercivity than commercial SmFeN powder even after heat-resistance tests in which the powders were annealed at 300°C for 1.5 h under Ar atmosphere. 22,23) We also found that pure SmFeN powder without any additive element prepared by the developed RD process exhibited high coercivity after the heat-resistance test. These results indicated that the improved heat resistance of the SmFeN powder was attributable to washing with EG in a GB.…”
Section: Introductionmentioning
confidence: 68%
“…1721) Our group previously adopted an RD process to prepare Sm 2 Fe 17 N x /Sm 2 (Fe,M) 17 N x (M = Mn or Cr) core shell fine powders that simultaneously exhibited high heat resistance and high saturation magnetization. 22,23) In our RD process, powder mixtures of Sm 2 Fe 17 After annealing, the powders were subjected to nitriding 24) to yield the Sm 2 Fe 17 N x /Sm 2 (Fe,M) 17 N x coreshell structures. In our method, ethylene glycol (EG) was used as the washing solvent instead of water to remove the CaO from the nitrided Sm 2 Fe 17 N x /Sm 2 (Fe,M) 17 N x coreshell powders.…”
Section: Introductionmentioning
confidence: 99%